Salt Stress Affects the Redox Status of Arabidopsis Root Meristems - Jiang, Keni; Moe-Lange, Jacob; Hennet, Lauriane; Feldman, Lewis J. (Frontiers in Plant Science, 2016)
We report the redox status (profiles) for specific populations of cells that comprise the Arabidopsis root tip. For recently germinated, 3-5-day-old seedlings we show that the region of the root tip with the most reduced redox status includes the root cap initials, the quiescent center and the most distal portion of the proximal meristem, and coincides with (overlays) the region of the auxin maximum. As one moves basally, further into the proximal meristem, and depending on the growth conditions, the redox status becomes more oxidized, with a 5-10 mV difference in redox potential between the two borders delimiting the proximal meristem. At the point on the root axis at which cells of the proximal meristem cease division and enter the transition zone, the redox potential levels off and remains more or less unchanged throughout the transition zone. As cells leave the transition zone and enter the zone of elongation the redox potentials become more oxidized. Treating roots with salt (50, 100 and 150 mM NaCl) results in marked changes in root meristem structure and development, and is preceded by changes in the redox profile, which flattens, and initially becomes more oxidized, with pronounced changes in the redox potentials of the root cap, the root cap initials and the quiescent center. Roots exposed to relatively mild levels of salt (< 100 mM) are able to re-establish a normal, pre-salt treatment redox profile 3-6 days after exposure to salt. Coincident with the salt-associated changes in redox profiles are changes in the distribution of auxin transporters (AUX1, PIN1/2), which become more diffuse in their localization. We conclude that salt stress affects root meristem maintenance, in part, through changes in redox and auxin transport.